Transanal protrusion of ventriculoperitoneal shunt reflecting asymptomatic perforation of the large bowel. (14th May 2014) - Plummer, Nicholas Russell; Tokala, Ajay; Date, Ravindra S
Abstract : Perforation into the gastrointestinal tract is a rare complication of ventriculoperitoneal shunt insertion. We present a case of transanal protrusion of the shunt catheter in an otherwise asymptomatic patient, with only transient signs of shunt failure some 2 months prior to presentation, and discuss treatment options to rationalise our decision to treat with laparotomy and preservation of the shunt.